A moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating and preparation method thereof

By using materials such as epoxy resin and modified filler in the current transformer coil coating, combined with the molecular connection effect of functional additives, the shortcomings of existing coatings in corrosion resistance and aging resistance are solved, and the problem of this coating is achieved. Higher mechanical and corrosion resistance.

CN118879161BActive Publication Date: 2025-02-07SHENZHEN CHUANGYIN TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411188583.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-02-07
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The existing current transformer coil coatings have shortcomings in corrosion resistance, aging resistance, moisture resistance, mildew resistance and light resistance, which limits its application areas and environment.

Method used

Using epoxy resin as the base composite coating, adding modification fillers, functional additives and other additives to enhance the mechanical properties and resistance of the coating through the molecular connection of the composite particle structure of the modified fillers and the functional additives. Corrosion performance.

Benefits of technology

It significantly improves the mechanical, corrosion resistance, aging resistance, moisture resistance and mildew resistance of the coating, meets higher performance needs and has excellent application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of coatings, and in particular to a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating and its preparation method. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating, in parts by mass, has the following raw materials: 90 to 110 parts of epoxy resin, 15 to 30 parts of modified filler, 5 to 10 parts of curing agent, 5 to 15 parts of toughening agent, 1 to 3 parts of leveling agent, 1 to 3 parts of defoaming agent, 5 to 10 parts of dispersant, 10 to 30 parts of diluent, 0.5 to 1.2 parts of mildewproof agent, and 5 to 15 parts of functional additives. The current transformer coil coating prepared by the present application can not only have excellent mechanical properties, but also can greatly increase the corrosion resistance, aging resistance, moisture resistance and mildew resistance of the coating, thereby meeting the performance requirements of the current transformer coil coating in the existing use environment, and has a very excellent application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and in particular to a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating and a preparation method thereof. Background Art

[0002] Current transformers are devices used to convert large currents into small currents for measurement and control, and they play a vital role in power systems. To ensure the stability and reliability of current transformers, the coils usually need to be treated with special coatings. These coatings are mainly responsible for providing insulation, physical protection, and corrosion protection.

[0003] One of the main purposes of current transformer coil coating is to provide good insulation performance and physical protection to ensure the safe and stable operation of the current transformer. However, with the development of technology and the iteration of product updates, consumers and manufacturers have higher and higher requirements for current transformer coils, which drives the performance requirements of current transformer coil coatings to become higher and higher.

[0004] At present, the current transformer coil coating in the existing technology focuses on using coating materials with better insulation, thermal stability, mechanical properties and low cost, and ignores the construction of coating corrosion resistance, aging resistance, moisture resistance, mildew resistance and light resistance. This not only greatly limits the application field and environment of the coating itself, but also the current transformer coil.

[0005] Therefore, in order to effectively solve the above problems, the present application provides a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating and a preparation method thereof. The current transformer coil coating prepared in the present application can not only maintain the insulation of the coating, but also greatly increase the mechanical properties, corrosion resistance, aging resistance, moisture resistance and mildew resistance of the coating, thereby meeting the performance requirements of the current transformer coil coating in the existing use environment, and has very excellent application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating. The raw materials are, by mass: 90~110 parts of epoxy resin, 15~30 parts of modified filler, 5~10 parts of curing agent, 5~15 parts of toughening agent, 1~3 parts of leveling agent, 1~3 parts of defoaming agent, 5~10 parts of dispersant, 10~30 parts of diluent, 0.5~1.2 parts of mildew inhibitor, and 5~15 parts of functional additives.

[0007] As a preferred solution, the mass ratio of the epoxy resin, the modified filler and the dispersant is (92-105): (18-25): (7-9).

[0008] As a preferred solution, the mass ratio of the epoxy resin, the modified filler and the dispersant is (95-100): (20-22): (7.5-8.5).

[0009] As a preferred solution, the mass ratio of the epoxy resin, toughening agent and functional additive is (92-105): (8-13): (10-14).

[0010] As a preferred solution, the mass ratio of the epoxy resin, toughening agent and functional additive is (95-100): (9-11): (11-13).

[0011] As a preferred solution, the epoxy resin is a composition of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin and phenolic modified epoxy resin.

[0012] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin and phenolic modified epoxy resin is (4-6): (2-3): (0.5-1.5).

[0013] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin and phenolic modified epoxy resin is (5-5.5): (2.2-2.5): (0.8-1).

[0014] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 170-220 g / eq.

[0015] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 185-195 g / eq.

[0016] As a preferred solution, the epoxide equivalent of the hydrogenated bisphenol A epoxy resin is 200-230 g / eq.

[0017] As a preferred solution, the epoxide equivalent of the hydrogenated bisphenol A epoxy resin is 210-220 g / eq.

[0018] As a preferred solution, the viscosity of the hydrogenated bisphenol A epoxy resin is 1500-4000 cPs at 25°C.

[0019] As a preferred solution, the viscosity of the hydrogenated bisphenol A epoxy resin is 2000-3000 cPs at 25°C.

[0020] As a preferred solution, the preparation method of the modified filler comprises the following steps: S1: adding sericite powder to a mixed solution of ethanol and deionized water, adding ammonia water to adjust the pH to 9.5-10.5, then adding ethyl orthosilicate and triethanolamine and heating to 60-65°C for 1.5-2h, after completion, centrifuging and filtering the product, washing it with ethanol for 2-3 times, and vacuum drying to obtain pretreated sericite powder; S2: adding the pretreated sericite powder to a mixed solution of DMF and deionized water, adding succinic anhydride, sodium dodecyl sulfonate and silane coupling agent, heating to The reaction was carried out at 70-75°C for 3-3.5 hours to obtain pretreated particles; S3: the pretreated particles were mixed with 2,5-dihydroxyterephthalic acid, added to the DMF solution, stirred evenly, and ultrasonically dispersed at 200-300W for 30-40 minutes. After the dispersion was completed, the temperature was raised to 70-80°C and a DMF solution containing zinc acetate was added dropwise, and the temperature was kept for 2-3 hours. Then, the temperature was continued to be raised to 120-130°C, and the reaction was stirred at 80-100rpm for 28-34 hours. After completion, it was naturally cooled to room temperature. After the product was centrifuged and filtered, it was washed with methanol for 2-4 times and vacuum dried to obtain the product.

[0021] As a preferred solution, the mass ratio of the sericite powder, tetraethyl orthosilicate and triethanolamine is (4-4.5): (0.3-0.5): (0.1-0.15).

[0022] As a preferred solution, the mass ratio of the pretreated sericite powder, succinic anhydride, sodium dodecyl sulfonate and silane coupling agent is (5-5.5): (1.2-1.5): (0.3-0.5): (0.2-0.3).

[0023] As a preferred solution, the silane coupling agent is γ-glycidyloxypropylmethyldimethoxysilane.

[0024] As a preferred solution, in the pretreated particles, the mass ratio of 2,5-dihydroxyterephthalic acid and zinc acetate is (4.5-5): (1.2-1.5): (0.4-0.6).

[0025] As a preferred solution, the average particle size of the sericite powder is 1.5-2.5 μm.

[0026] As a preferred solution, in the mixed solution of ethanol and deionized water, the mass ratio of ethanol to deionized water is (4-5):1.

[0027] As a preferred solution, in the mixed solution of DMF and deionized water, the mass ratio of DMF to deionized water is (2-3):1.

[0028] In the present application, the addition of the above-mentioned modified filler can effectively improve the mechanical, corrosion resistance, aging resistance and waterproof and moisture-proof properties of the coating. The added modified filler can use the flaky structure of sericite powder as a base template, and through the surface coating of amorphous silica and the active modification of surface hydroxyl groups, the connection strength of sericite powder to subsequent framework particles is greatly enhanced, so that a stable framework particle loading structure is formed on the surface of sericite powder. The existence of the composite structure can form a stacking phenomenon of the filler through the good spreading effect of the sericite powder base in the coating system, and then through the surface roughness and the formed combined stacking, the free speed of active molecules and water molecules in the coating is greatly reduced, the number of internal active groups is reduced, the penetration resistance of water molecules is increased, and the surface roughness of the coating is reduced. The efficiency of the surface hydration layer formation is reduced, and the internal space steric hindrance is increased to avoid the deterioration reaction of external corrosion molecules and internal active molecules during long-term use, thereby obtaining excellent corrosion resistance, aging resistance, and waterproof and moisture-proof properties; and the modified groups present in the composite particle structure can greatly enhance the strength of the molecular chain network inside the coating through the molecular connection with the functional additives and the epoxy coating system in the present application, thereby obtaining good mechanical properties.

[0029] As a preferred solution, the curing agent is at least one of diethylenetriamine, dimethylethanolamine, 1,3-diaminocyclohexane, m-phenylenediamine, and 4,4'-diaminodiphenyl sulfone.

[0030] As a preferred solution, the curing agent is diethylenetriamine or 1,3-diaminocyclohexane.

[0031] As a preferred solution, the toughening agent is at least one of liquid nitrile rubber, liquid polysulfide rubber, and liquid polyurethane rubber.

[0032] As a preferred solution, the toughening agent is liquid nitrile rubber.

[0033] As a preferred solution, the leveling agent is at least one of a polysiloxane leveling agent, an acrylate leveling agent, and a polyether leveling agent.

[0034] As a preferred solution, the leveling aid is a polysiloxane leveling agent.

[0035] As a preferred solution, the defoaming agent is at least one of silicone defoaming agents.

[0036] As a preferred solution, the dispersant is at least one of lauryl alcohol polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, sodium stearate, alkyl glucoside, and coconut oil betaine.

[0037] As a preferred solution, the dispersant is a combination of lauryl alcohol polyoxyethylene ether and sodium stearate.

[0038] As a preferred solution, the mass ratio of lauryl alcohol polyoxyethylene ether to sodium stearate is (4-4.5): (1.5-1.8).

[0039] As a preferred solution, the diluent is a combination of butanol and isopropanol.

[0040] As a preferred solution, the mass ratio of butanol to isopropanol is (5-7):(1-1.5).

[0041] As a preferred solution, the mildew inhibitor is at least one of isothiazolinones and benzoates.

[0042] As a preferred solution, the mildew inhibitor is sodium benzoate or potassium benzoate.

[0043] As a preferred solution, the functional auxiliary agent is a composition of epoxy block polymer, polytetramethylene ether glycol bis-p-aminobenzoate and pullulan.

[0044] As a preferred solution, the mass ratio of the epoxy block polymer to the amylopectin is (6-8):(1-2):(0.3-0.6).

[0045] As a preferred solution, the mass ratio of the epoxy block polymer to the amylopectin is (6.5-7): (1.2-1.6): (0.4-0.5).

[0046] As a preferred solution, the epoxy block polymer is a composition of an ethylene oxide-propylene oxide block polyether with a weight average molecular weight of 2500-3500 and an ethylene oxide-propylene oxide block polyether with a weight average molecular weight of 8000-11000.

[0047] As a preferred solution, the mass ratio of the ethylene oxide-propylene oxide block polyether with a weight average molecular weight of 2500-3500 to the ethylene oxide-propylene oxide block polyether with a weight average molecular weight of 8000-11000 is (6-7):(1.5-2).

[0048] As a preferred solution, the viscosity of the polytetramethylene ether glycol bis-p-aminobenzoate is 3000-5000 mPa·s at 30°C.

[0049] As a preferred solution, the branched chain content of the amylopectin is 70-80%.

[0050] The above-mentioned composite functional additives added in this application can effectively improve the corrosion resistance, waterproof, moisture-proof and aging resistance of the overall coating while ensuring that the coating has good mechanical properties. The combined effect of the epoxy block polymer and polytetramethylene ether glycol bis-p-aminobenzoate added in this application can serve as an excellent carrier of the modified filler, and can strengthen the fixation of the modified filler after the dispersion and curing of the coating by participating in the reaction of the epoxy group, greatly reducing its agglomeration, segregation and migration phenomena, and greatly enhancing the entanglement of the molecular chains inside the coating system through the branched connection of amylopectin and the effect of participating in epoxy curing, and can use the multi-branched structure of amylopectin as a connecting bridge to greatly improve the internal connection force and molecular chain density, reduce the probability of molecular collision, and then obtain excellent mechanical, corrosion resistance, aging resistance and moisture and waterproof properties.

[0051] The second aspect of the present application provides a method for preparing the above-mentioned moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating, which specifically includes the following steps: S1: Add epoxy resin to a stirring container, add a curing agent, a toughening agent and a mixture of a modified filler and a dispersant and a functional additive in sequence, stir and mix evenly at 60~80rpm until there are no obvious particles, and then add a diluent to adjust the overall viscosity; S2: After heating to 45~50℃, add a leveling agent, a defoaming agent and a mildewproof agent, stir at 100~120rpm for 40~55min, then naturally cool to room temperature, stand for 15~20min to defoam, and obtain a coating; S3: Evenly apply the coating on the surface of the current transformer coil, control the thickness to 0.1~0.15mm, then place the current transformer coil in an oven, heat to 100~120℃, keep for 2~3 hours for initial curing, then heat to 140~150℃, and keep for 2~3 hours to complete final curing.

[0052] The beneficial effects of this application are:

[0053] 1. The present application provides a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating, which can not only maintain the insulation of the coating, but also greatly increase the mechanical properties, corrosion resistance, aging resistance, moisture resistance and mildew resistance of the coating, thereby meeting the performance requirements of the current transformer coil coating in the existing use environment and having excellent application prospects.

[0054] 2. A moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating provided in the present application, wherein the added modified filler can use the flaky structure of sericite powder as a base template, and through the surface coating of amorphous silica and the active modification of the surface hydroxyl groups, the connection strength of the sericite powder to the subsequent framework particles is greatly enhanced, thereby forming a stable framework particle loading structure on the surface of the sericite powder. The existence of the composite structure can form a stacking phenomenon of the filler through the good spreading effect of the sericite powder substrate in the coating system, and then through the surface roughness and the formed combined stacking, the free speed of active molecules and water molecules in the coating is greatly reduced, the number of internal active groups is reduced, the penetration resistance of water molecules is increased, and the surface roughness of the coating is reduced. The efficiency of the surface hydration layer formation is reduced, and the internal space steric hindrance is increased to avoid the deterioration reaction of external corrosion molecules and internal active molecules during long-term use, thereby obtaining excellent corrosion resistance, aging resistance, and waterproof and moisture-proof properties.

[0055] 3. A moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating provided in the present application, the modified groups on the composite particle structure of the added modified filler can greatly enhance the molecular chain network strength inside the coating through the molecular connection with the functional additives and the epoxy coating system in the present application, thereby obtaining good mechanical properties.

[0056] 4. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating provided in the present application, in which the added epoxy block polymer and polytetramethylene ether glycol di-p-aminobenzoate can act together as an excellent carrier of the modified filler, and can enhance the fixation of the modified filler after dispersion and curing of the coating by participating in the reaction of the epoxy group, thereby greatly reducing its agglomeration, segregation and migration phenomena, and through the branch connection effect of amylopectin and the effect of participating in epoxy curing, the entanglement degree of the molecular chains inside the coating system is greatly enhanced, and the multi-branched structure of amylopectin can be used as a connecting bridge to greatly improve the internal connection force and the density of the molecular chain, reduce the probability of molecular collision, and thereby obtain excellent mechanical, corrosion and aging resistance, and moisture and waterproof properties. DETAILED DESCRIPTION

[0057] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0058] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0059] Example 1

[0060] The first aspect of Example 1 provides a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating. The raw materials, in parts by mass, are: 98.5 parts of epoxy resin, 21.5 parts of modified filler, 6.8 parts of curing agent, 10.5 parts of toughening agent, 2.1 parts of leveling agent, 1.2 parts of defoaming agent, 8.2 parts of dispersant, 15.6 parts of diluent, 0.6 parts of mildewproof agent, and 12.5 parts of functional additives.

[0061] The epoxy resin is a composition of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin and phenolic modified epoxy resin, and the mass ratio of the three is 5.2:2.4:0.8.

[0062] The epoxy equivalent of bisphenol A epoxy resin is 192 g / eq, and the product of model E-51 was purchased from Baling Petrochemical.

[0063] The epoxy equivalent of hydrogenated bisphenol A epoxy resin is 215 g / eq. The EP-4080E product purchased from Shanghai Kaiyin Chemical has a viscosity of 2400 cPs at 25°C.

[0064] The phenolic modified epoxy resin was purchased from the 704 type epoxy resin product sold by Baling Petrochemical.

[0065] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 4.2 parts of sericite powder to a mixed solution of 120 parts of ethanol and deionized water, adding ammonia water to adjust the pH to 9.8, then adding 0.45 parts of ethyl orthosilicate and 0.12 parts of triethanolamine and heating to 62°C for 1.8 hours, after completion, centrifuging and filtering the product, washing it twice with ethanol, and vacuum drying to obtain pretreated sericite powder; S2: adding 5.1 parts of pretreated sericite powder to a mixed solution of 120 parts of DMF and deionized water, adding 1.46 parts of succinic anhydride, 0.32 parts of dodecyl Sodium sulfonate and 0.26 parts of silane coupling agent, heated to 75°C and kept warm for 3 hours to obtain pretreated particles; S3: 4.8 parts of pretreated particles and 1.45 parts of 2,5-dihydroxyterephthalic acid were mixed and added to 80 parts of DMF solution, stirred evenly and ultrasonically dispersed at 250W power for 35 minutes. After the dispersion was completed, the temperature was raised to 75°C and a DMF solution containing 0.55 parts of zinc acetate (a total of 15 parts) was added dropwise, and the temperature was kept for 3 hours. Then, the temperature was continued to be raised to 128°C, stirred at 80rpm for 30 hours, and naturally cooled to room temperature after completion. The product was centrifuged and filtered, washed with methanol for 3 times and vacuum dried to obtain.

[0066] The silane coupling agent is γ-glycidyloxypropylmethyldimethoxysilane; and the average particle size of the sericite powder is 1.8 μm.

[0067] In the mixed solution of ethanol and deionized water, the mass ratio of ethanol to deionized water is 4:1; in the mixed solution of DMF and deionized water, the mass ratio of DMF to deionized water is 2:1.

[0068] The curing agent is diethylenetriamine.

[0069] The toughening agent is a toughening agent, specifically liquid nitrile rubber, purchased from Hengshui Chituma New Materials Co., Ltd., a LR820 model product.

[0070] The leveling agent is polysiloxane leveling agent BYK-333.

[0071] The defoamer is silicone defoamer BYK-066N.

[0072] The dispersant is a composition of lauryl alcohol polyoxyethylene ether and sodium stearate, with a mass ratio of 4.4:1.6; lauryl alcohol polyoxyethylene ether was purchased from the MOA-5 model product sold by Hai'an Guoyun Chemical Co., Ltd.

[0073] The diluent is a combination of butanol and isopropanol, and the mass ratio of the two is 6:1.2.

[0074] The mildew inhibitor is sodium benzoate.

[0075] The functional additive is a composition of epoxy block polymer, polytetramethylene ether glycol bis-p-aminobenzoate and pullulan, and the mass ratio of the three is 6.8:1.4:0.4.

[0076] The epoxy block polymer is a composition of ethylene oxide-propylene oxide block polyether (BASF L64) with a weight average molecular weight of 2900 and ethylene oxide-propylene oxide block polyether (BASF L88) with a weight average molecular weight of 10800, and the mass ratio of the two is 6.5:1.5.

[0077] Polytetramethylene ether glycol bis-p-aminobenzoate was purchased from Suzhou Xiangyuan New Materials Co., Ltd. and sold as Xylink P-1000, with a viscosity of 4200 mPa·s at 30°C.

[0078] The amylopectin was purchased from amylopectin product sold by Shandong West Asia Chemical, and its amylopectin content was 71.6%.

[0079] The second aspect of the present embodiment provides a method for preparing a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating, which specifically includes the following steps: S1: Add epoxy resin to a stirring container, and add a curing agent, a toughening agent, and a mixture of a modified filler and a dispersant and a functional additive in turn, stir and mix evenly at 80rpm until there are no obvious particles, and then add a diluent to adjust the overall viscosity; S2: After heating to 45°C, add a leveling agent, a defoaming agent and a mildewproof agent, stir at 100rpm for 50min, then naturally cool to room temperature, stand for 20min to defoam, and obtain a coating; S3: Evenly apply the coating on the surface of the current transformer coil, controlling the thickness to 0.1mm, then placing the current transformer coil in an oven, heating to 110°C, keeping for 3 hours for initial curing, then heating to 145°C, and keeping for another 3 hours to complete final curing.

[0080] Example 2

[0081] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating comprises, by weight, 105 parts of epoxy resin, 18 parts of modified filler, 6.8 parts of curing agent, 8.2 parts of toughening agent, 2.1 parts of leveling agent, 1.2 parts of defoaming agent, 7 parts of dispersant, 15.6 parts of diluent, 0.6 parts of mildew inhibitor and 10.5 parts of functional additive.

[0082] Comparative Example 1

[0083] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating, in parts by mass, comprises the following raw materials: 120 parts of epoxy resin, 10 parts of modified filler, 6.8 parts of curing agent, 10.5 parts of toughening agent, 2.1 parts of leveling agent, 1.2 parts of defoaming agent, 8.2 parts of dispersant, 15.6 parts of diluent, 0.6 parts of mildew inhibitor and 18.5 parts of functional additive.

[0084] Comparative Example 2

[0085] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating, in parts by mass, comprises the following raw materials: 98.5 parts of epoxy resin, 28.5 parts of modified filler, 6.8 parts of curing agent, 10.5 parts of toughening agent, 2.1 parts of leveling agent, 1.2 parts of defoaming agent, 8.2 parts of dispersant, 15.6 parts of diluent, 0.6 parts of mildew inhibitor and 6.5 parts of functional additive.

[0086] Comparative Example 3

[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy resin is a composition of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin and phenolic modified epoxy resin, and the mass ratio of the three is 7.5:1:0.2.

[0088] Comparative Example 4

[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 4.2 parts of sericite powder to a mixed solution of 120 parts of ethanol and deionized water, adding ammonia water to adjust the pH to 9.8, then adding 0.15 parts of ethyl orthosilicate and 0.04 parts of triethanolamine and heating to 62°C for 2 hours, after completion, centrifuging and filtering the product, washing it twice with ethanol, and vacuum drying to obtain pretreated sericite powder; S2: adding 6.8 parts of pretreated sericite powder to a mixed solution of 120 parts of DMF and deionized water, adding 0.85 parts of DMF and deionized water; Dianhydride, 0.15 parts of sodium dodecyl sulfonate and 0.12 parts of silane coupling agent, heated to 75°C and kept warm for 3 hours to obtain pretreated particles; S3: 4.8 parts of pretreated particles and 1.45 parts of 2,5-dihydroxyterephthalic acid were mixed and added to 80 parts of DMF solution, stirred evenly and ultrasonically dispersed at 250W power for 35 minutes. After the dispersion was completed, the temperature was raised to 75°C and a DMF solution containing 0.55 parts of zinc acetate (a total of 15 parts) was added dropwise, and the temperature was kept for 3 hours. Then, the temperature was continued to be raised to 128°C, stirred at 80rpm for 30 hours, and naturally cooled to room temperature after completion. The product was centrifuged and filtered, washed with methanol for 3 times and vacuum dried to obtain.

[0090] Comparative Example 5

[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, measured in parts by mass: S1: adding 4.2 parts of sericite powder to a mixed solution of 120 parts of ethanol and deionized water, adding ammonia water to adjust the pH to 9.8, then adding 0.45 parts of ethyl orthosilicate and 0.12 parts of triethanolamine and heating to 62°C for 1.8 hours, after completion, centrifuging and filtering the product, washing it twice with ethanol, and vacuum drying to obtain pretreated sericite powder; S2: adding 5.1 parts of pretreated sericite powder to a mixed solution of 120 parts of DMF and deionized water, adding 1.46 parts of Succinic anhydride, 0.32 parts of sodium dodecyl sulfonate and 0.26 parts of silane coupling agent, heated to 75°C and kept warm for 3 hours to obtain pretreated particles; S3: 7.5 parts of pretreated particles and 1.05 parts of 2,5-dihydroxyterephthalic acid were mixed and added to 120 parts of DMF solution, stirred evenly and ultrasonically dispersed at 250W power for 35 minutes. After the dispersion was completed, the temperature was raised to 75°C and a DMF solution containing 0.28 parts of zinc acetate (a total of 10 parts) was added dropwise, and the temperature was kept for 3 hours. Then, the temperature was continued to be raised to 128°C, stirred at 80rpm for 30 hours, and naturally cooled to room temperature after completion. The product was centrifuged and filtered, washed with methanol for 3 times and vacuum dried to obtain.

[0092] Comparative Example 6

[0093] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of the sericite powder is 6.5 μm.

[0094] Comparative Example 7

[0095] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional auxiliary agent is a composition of epoxy block polymer, polytetramethylene ether glycol bis-p-aminobenzoate and pullulan, and the mass ratio of the three is 8.5:0.5:0.2.

[0096] Comparative Example 8

[0097] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy block polymer is a composition of ethylene oxide-propylene oxide block polyether (BASF L64) with a weight average molecular weight of 2900 and ethylene oxide-propylene oxide block polyether (BASF L88) with a weight average molecular weight of 10800, and the mass ratio of the two is 12:1.

[0098] Performance Evaluation

[0099] Folding resistance: The coatings prepared in the examples and comparative examples were tested for folding resistance. The coatings were folded inside out at 180° for 20 times and then peeled off with tape. The area rate of coating shedding at the crease was measured. The measured values ​​were taken as the average value of 10 groups of tests and recorded in Table 1.

[0100] Salt spray resistance test: The coatings prepared in the embodiments and comparative examples were subjected to a salt spray resistance test. The test environment temperature was 35±2°C, the humidity was 98±2%, the test solution was 5wt% NaCl solution, and the test time was 350h. After the test, the coating was observed for corrosion, shedding, cracking, and blistering. If any, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the qualified rate was recorded in Table 1.

[0101] Aging resistance test: The coatings prepared in the embodiments and comparative examples were subjected to an aging resistance test in a constant temperature and humidity chamber. The test environment temperature was 65±2°C, the humidity was 75±2%, and the test time was 30 days. After the 30-day test, the coatings were observed for oxidation, yellowing, shedding, and blistering. If so, they were marked as unqualified, otherwise qualified. 50 samples were tested in each group, and the qualified rate was recorded in Table 1.

[0102] Waterproof test: The coatings prepared in the examples and comparative examples were tested for water resistance by using the sessile drop method. A 2 μL water drop was used for 10 s to obtain the water contact angle value on the coating surface. The test value was the average of 10 tests and recorded in Table 1.

[0103] Mildew resistance test: The mildew resistance of the coatings prepared in the embodiments and comparative examples was tested with reference to the standard GB / T 1741-2020. The test environment temperature was 28±2°C, the humidity was 98±2%, the incubation time was 28d, and the test values ​​were the average of 10 tests and recorded in Table 1.

[0104] Table 1 Performance test results

[0105]

[0106] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 8 in terms of mechanical properties, waterproof and moisture-proof properties, corrosion resistance and aging resistance. This is mainly due to the combined effect of the modified fillers, functional additives and other matching technical solutions specified in the present application. Comparative examples 1 to 8 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating, characterized in that: In parts by mass, the raw materials are: 90-110 parts of epoxy resin, 15-30 parts of modified filler, 5-10 parts of curing agent, 5-15 parts of toughening agent, 1-3 parts of leveling agent, 1-3 parts of defoaming agent, 5-10 parts of dispersant, 10-30 parts of diluent, 0.5-1.2 parts of mildewproof agent, and 5-15 parts of functional additives; The mass ratio of the epoxy resin, the modified filler and the dispersant is (92-105):(18-25):(7-9); The mass ratio of the epoxy resin, toughening agent and functional additive is (92-105): (8-13): (10-14); The epoxy resin is a composition of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin and phenolic modified epoxy resin; The mass ratio of the bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin and phenolic modified epoxy resin is (4-6): (2-3): (0.5-1.5); Preparation method of the modified filler The following steps are involved: S1: Add sericite powder to a mixed solution of ethanol and deionized water, add ammonia water to adjust the pH to 9.5-10.5, then add ethyl orthosilicate and triethanolamine and heat to 60-65°C for 1.5-2h. After completion, centrifuge and filter the product, wash it with ethanol for 2-3 times, and vacuum dry it to obtain the pretreated sericite powder; S2: Add the pretreated sericite powder to a mixed solution of DMF and deionized water, add succinic anhydride, sodium dodecyl sulfonate and silane coupling agent, heat to 70-75°C and keep warm for 3-3.5 hours to obtain pretreated particles; S3: Mix the pretreated particles with 2,5-dihydroxyterephthalic acid, add to the DMF solution, stir evenly and ultrasonically disperse at 200-300W power for 30-40 minutes. After dispersion, heat to 70-80°C and dropwise add DMF solution containing zinc acetate, keep warm for 2-3 hours, then continue to heat to 120-130°C, stir at 80-100rpm for 28-34 hours, and naturally cool to room temperature after completion. After centrifugal filtration, the product is washed with methanol for 2-4 times and vacuum dried to obtain; The mass ratio of the sericite powder, tetraethyl orthosilicate and triethanolamine is (4-4.5): (0.3-0.5): (0.1-0.15); The mass ratio of the pretreated sericite powder, succinic anhydride, sodium dodecyl sulfonate and silane coupling agent is (5-5.5): (1.2-1.5): (0.3-0.5): (0.2-0.3); In the pretreated particles, the mass ratio of 2,5-dihydroxyterephthalic acid to zinc acetate is (4.5-5):(1.2-1.5):(0.4-0.6); The curing agent is at least one of diethylenetriamine, dimethylethanolamine, 1,3-diaminocyclohexane, m-phenylenediamine, and 4,4'-diaminodiphenyl sulfone; The toughening agent is at least one of liquid nitrile rubber, liquid polysulfide rubber, and liquid polyurethane rubber; The leveling agent is at least one of a polysiloxane leveling agent, an acrylate leveling agent, and a polyether leveling agent.

2. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 1, characterized in that: The epoxy equivalent of the bisphenol A epoxy resin is 170-220 g / eq.

3. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 2, characterized in that: The epoxy equivalent of the hydrogenated bisphenol A epoxy resin is 200-230 g / eq.

4. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 3, characterized in that: The viscosity of the hydrogenated bisphenol A epoxy resin is 1500-4000 cPs at 25°C.

5. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 4, characterized in that: The average particle size of the sericite powder is 1.5-2.5 μm.

6. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 5, characterized in that: The leveling aid is a polysiloxane leveling agent.

7. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 6, characterized in that: The dispersant is at least one of lauryl alcohol polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, sodium stearate, alkyl glucoside, and coconut oil betaine.

8. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 7, characterized in that: The diluent is a composition of butanol and isopropanol; the mass ratio of butanol to isopropanol is (5-7):(1-1.5).

9. The moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to claim 8, characterized in that: The functional auxiliary agent is a composition of epoxy block polymer, polytetramethylene ether glycol bis-p-aminobenzoate and pullulan; the mass ratio of the epoxy block polymer to the pullulan is (6-8): (1-2): (0.3-0.6).

10. A method for preparing a moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Add epoxy resin to a stirring container, add curing agent, toughening agent, and a mixture of modified filler, dispersant, and functional additives in sequence, stir and mix at 60-80 rpm until no obvious particles are present, and then add diluent to adjust the overall viscosity; S2: After heating to 45~50℃, add leveling agent, defoaming agent and mildewproof agent, stir at 100~120rpm for 40~55min, cool naturally to room temperature, stand for 15~20min to defoam, and obtain coating; S3: Apply the coating evenly on the surface of the current transformer coil, control the thickness to 0.1~0.15mm, then place the current transformer coil in an oven, heat to 100~120℃, keep for 2~3 hours for initial curing, then heat to 140~150℃, and keep for 2~3 hours to complete final curing.

Citation Information

Patent Citations

  • High-weather-resistance long-acting anticorrosive epoxy coating for inner wall of wind power tower drum and preparation method of long-acting anticorrosive epoxy coating

    CN113402947A

  • High-temperature-resistant and high-pressure-resistant hot-fritting epoxy powder coating for pipeline corrosion prevention

    CN115044273A